2013
DOI: 10.1371/journal.pone.0052945
|View full text |Cite|
|
Sign up to set email alerts
|

Acute Stress Induces Hyperacusis in Women with High Levels of Emotional Exhaustion

Abstract: BackgroundHearing problems is one of the top ten public health disorders in the general population and there is a well-established relationship between stress and hearing problems. The aim of the present study was to explore if an acute stress will increase auditory sensitivity (hyperacusis) in individuals with high levels of emotional exhaustion (EE).MethodsHyperacusis was assessed using uncomfortable loudness levels (ULL) in 348 individuals (140 men; 208 women; age 23–71 years). Multivariate analyses (ordere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 48 publications
(58 reference statements)
6
28
0
Order By: Relevance
“…Twelve of our patients with severe hyperacusis had a history of mental health problems and six of them were taking antidepressants. This is consistent with past studies that suggest a relationship between hyperacusis and mental health problems (Aazh & Allott, 2016;Aazh et al, 2014;Dubal & Viaud-Delmon, 2008;Goebel & Floezinger, 2008;Hasson et al, 2013;Juris et al, 2013). This highlights the need for psychiatric evaluation and treatment (when needed) of patients with severe hyperacusis.…”
Section: Table 3 Heresupporting
confidence: 91%
“…Twelve of our patients with severe hyperacusis had a history of mental health problems and six of them were taking antidepressants. This is consistent with past studies that suggest a relationship between hyperacusis and mental health problems (Aazh & Allott, 2016;Aazh et al, 2014;Dubal & Viaud-Delmon, 2008;Goebel & Floezinger, 2008;Hasson et al, 2013;Juris et al, 2013). This highlights the need for psychiatric evaluation and treatment (when needed) of patients with severe hyperacusis.…”
Section: Table 3 Heresupporting
confidence: 91%
“…Whilst its causes are not always clearly identifiable and closely interlinked, chronic tinnitus has been associated with numerous risk factors (Haider et al, 2018;Trevis et al, 2018;Boecking et al, 2019) that have partly been interpreted within a vulnerabilitystress framework. For example, emotional exhaustion and low emotional well-being were found to predict the risk of developing tinnitus (Hébert et al, 2012) with the former also being shown to predict higher sensitivity to sound following an acute stress task (Hasson et al, 2013). Moreover, several studies have shown that existing emotional distress predicted higher tinnitus-related distress (Bartels et al, 2009;Schaaf et al, 2014;Wallhäusser-Franke et al, 2015;Durai and Searchfield, 2016;Strumila et al, 2017;Sahlsten et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For an animal, moderate to high intensity noise could mask relevant acoustic cues that warn of an approaching predator, social communications or pup calls to its mother (Brouette-Lahlou et al, 1992; Brudzynski, 2009; Tennessen et al, 2016). Because high intensity noise increases corticosterone/cortisol stress hormones (Alario et al, 1987; De Boer et al, 1989; Hasson et al, 2013), sound-induced avoidance behavior may be linked to the degree of stress evoked by our 60 and 90 dB noise stimuli. Long-term noise exposures alter the adrenal cortex and corticosterone plasma levels (Soldani et al, 1999).…”
Section: Discussionmentioning
confidence: 99%